Early Onset and Severe Progression of Neuro-ophthalmological Manifestations in a Case with Parry–Romberg Syndrome - Zone Abid, Imen; Ben Nsir, Sihem; Jarrar, Emna; Feki, Jamel; Kamoun, Fatma; Triki, Chahnez (Journal of Pediatric Neurology, 2020)
Parry–Romberg syndrome is a rare disorder characterized by unilateral facial atrophy affecting the skin, subcutaneous tissue, and muscles, and sometimes extending to the osteocartilaginous structures. Ophthalmological and neurological involvements are relatively rare. We present a case of an early onset of left hemifacial atrophy, a progressive severe left ocular impairment, and the presence of a neurological disorder in the left hemisphere of the brain. The neuro-ophthalmological manifestations on the left side include enophthalmos, mild pseudoptosis, moderate asymmetry of the eyebrows, diffuse chorioretinal atrophy, reduced visual acuity, reduced central retinal thickness (162 µm) with the interruption of the ellipsoid zone, and the alteration of the outer nuclear layer, with associated reduced responses in photopic and scotopic amplitudes. The patient reported high intensity left brain white matter and a brief clinical focal seizure. This case report adds to the repertoire spectrum of this rare syndrome. The presentation calls for a multidisciplinary care for patients like our case.
Keywords: Parry–Rombergsyndrome; ophthalmology; neurology; early revelation